The simulation and design air conditioner in unit 103 of south pars with use advance exergy - Darabi, Mohsen; Mohammadiun, Mohammad; Mohammadiun, Hamid; Mortazavi, Saeed; Maddah, Heydar (International Journal of Scientific World, 2015)
In this paper, energy recycling for distillation tower condenser was done by use of heat integration method. At first, we calculated the amount of condensation energy (QAir Cooler), in air cooler, and then we calculated energy consumption in this equipment based on annual balance (5460 GJ per year). Then, based on heat integration (energy unification), two conditions were proposed to use the current energies in the process for supplying condensation energy (QAir Cooler): first, its must be lesser than condensing temperature of condenser (55 Â° C) (the major condition). Second, it must have much more flow rate than the overhead flow. According to two above conditions, the food flow as chosen as the integration factor and its amount of energy (EStream) is calculated from the Enthalpy equation as 9863964 kj/h. As EFeed >>> QAir Cooler and food flow temperature to condense an overhead vapor is satisfying. The food flow can be used to condense the saturated vapor to 55 Â° C. in case of using food energy and using heat exchanger instead of air cooler; 5460 GJ energy will be saved annually. By using heat exchanger and omitting air cooler, the unit103 operating costs will be reduced considerably. Economically, conducting such a project will demand investing costs. However, obtainable incomes from doing this project (electricity consumption recycling and cost's reduction) reveal this fact that capital return rate and the project benefits for unit103 of South Pars phases2&3 are beneficial.